Rethinking Resistance: Nonparticipation, Consumption, and the Recruitment of Affirmation in Internet Fandom - Stanfill, Mel; Booth, Paul; Bury, Rhiannon (AoIR Selected Papers of Internet Research, 2013)
In place of the presumption that digital media is always-already a space of production, participation, resistance, and appropriation, this panel seeks to enrich our understanding of fandom by exploring when and how other models—such as nonparticipation, consumption, and the positioning of audiences as consumers or as particular, limited types of participants—come into play. Panelist 1 examines “digital cosplay,” or fans’ use of Polyvore (an image-based online social media service) in the consumption and reproduction of media characters through the construction of outfits meant to represent them. This presentation argues that generating this imagery and identity is an act of consumption, as it necessarily imbricates the media text. Yet, at the same time it is also an act of appropriation, pushing media into a specific contour. As a form of consumptive reproduction, “digital cosplay” describes the playful re-creation of character outfits, clothing, and accessories using digital technology in online spaces in a way that is at once looking for fidelity as they consume the object of fandom in a nostalgic way and, paradoxically, engaged in the contemporary novelty of a makeover. Panelist 2 begins by taking issue with the way early studies of fandom assumed a participatory culture as the norm in a way that established a baseline for not only what constitutes a legitimate object of study—participatory fan culture—but also who gets classified as a legitimate fan. This assumption of participation has been further cemented with digital media, with a focus on fan uses of social networking and content-sharing sites. While our second panelist has presented such research, this presentation uses data from the same mixed-methods study to examine instead the invisible and devalued “non-participatory” fan. Panelist 2’s survey data are strongly suggestive that the participatory fan is in the minority, and interview data imply that most people are uninterested in going online to visit fan forums to interact with other fans they do not know, troubling assumptions about internet-era consumption in the form of regular viewing and participation. Panelist 3 contends that while transmedia is usually understood as a Web 2.0 phenomenon and as thus premised on an idea of interactivity, when it is orchestrated by media industries it is not so much interactive as reactive. Through an examination of web design for fans and industry statements about fans, the third panelist identifies official transmedia is inherently consumptive and thus usefully understood as Consumption 2.0. The presentation argues that transmedia is a means of pitching intensive engagement to fans in circumscribed ways, giving so that fans don’t have to bother taking, and introducing ease into the process of intensive engagement in a way that acts to shape desire and define fans as consumers. This panel provides us the opportunity to consider the limits and realities of digital media’s interactive potential, as we consider a wide range of modes and formats of fan interaction, including instances in which fan participation is notably absent or disciplined. In keeping with our collective interest in when and in what ways audiences can participate, this panel has an interactive format and exists as a hybrid of a panel and a roundtable. Panelists will keep their presentations short in order to open up a robust discussion between panelists and with attendees.